Assessment of Capacitance for Self-Excited Induction Generator in Sustaining Constant Air-Gap Voltage under Variable Speed and Load - Ashish Sharma; Gagandeep Kaur (Energies, 2018)
The concept of a Self-Excited Induction Generator (SEIG) has introduced the concept of the placement of an induction machine for power generation in an isolated mode with external capacitance. The produced output voltage and generated frequency in an SEIG greatly depends on speed, load, and terminal capacitance. To maintain constant air-gap voltage against a varying speed and load, a corresponding supply of reactive power through capacitors is needed. The selection of the required capacitance while there is continuous variation of vital parameters needs a rigorous random-selection method. In this paper, an intelligent selection of suitable additional capacitance has been made by using the Fuzzy Logic Technique for a Three-Phase 5.0 HP SEIG. Additional capacitance in the range of 14.79–22.47 μF is compulsory under a varying load of 427−101 ohms, and additional capacitance in the range of 13.70–22.59 μF is essential for a varying speed of 1349 to 1672 RPM. With this promising result, we propose the implementation of this intelligent technique in place of analytical and standard methods for capacitance selection.